2021
DOI: 10.3390/catal11050577
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Fe-Complexes on Oxide Surfaces for Efficient OER Catalysis

Abstract: Progress in non-covalent/self-assembled immobilization methods on (photo)electrode materials for molecular catalysts could broaden the scope of attainable systems. While covalent linkage (though considered more stable) necessitates functional groups introduced by means of often cumbersome synthetic procedures, non-covalent assemblies require sufficient propensity of the molecular unit for surface adsorption, thus set less rigorous pre-requisites. Herein, we report efficient electrodeposition (ED) of two Fe(III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…It can be found that Fe 0.5 h-SLCO shows the most excellent TOF, which further proves the high activity of Fe 0.5 h-SLCO. This is determined by the combination of the increase in specific surface area after delithiation and the increase of Fe 3+ active sites after Fe 3+ intercalation, which are beneficial to OER. , Also, Fe 0.5 h-SLCO shows better OER activity, which is comparable to or even better than that of the recovered LiCoO 2 catalysts and synthesized LiCoO 2 -based catalysts reported in other literature (Table S2).…”
Section: Resultsmentioning
confidence: 73%
“…It can be found that Fe 0.5 h-SLCO shows the most excellent TOF, which further proves the high activity of Fe 0.5 h-SLCO. This is determined by the combination of the increase in specific surface area after delithiation and the increase of Fe 3+ active sites after Fe 3+ intercalation, which are beneficial to OER. , Also, Fe 0.5 h-SLCO shows better OER activity, which is comparable to or even better than that of the recovered LiCoO 2 catalysts and synthesized LiCoO 2 -based catalysts reported in other literature (Table S2).…”
Section: Resultsmentioning
confidence: 73%
“…[72] Most recently, electrodeposition is also adopted to fabricate molecular precursors directly on the substrate for electrochemical studies. [75,76] Apart from these traditional methods, several advanced techniques have been used to produce nanomaterials, namely, thermolysis, solvolysis, and drop-casting. [77][78][79] It is worth mentioning here that MOFs is a different class of polymeric inorganic material, which is also analogous to SSP.…”
Section: Synthetic Methods To Derive Materials From Molecular Sspsmentioning
confidence: 99%
“…The electrocatalytic activities of stainless steel electrodes were studied in alkaline solution for OER. To evaluate catalytic performance, linear sweep voltammetry (LSV) is usually performed in alkaline solution by applying over the thermodynamic potential of OER (>1.23 V vs. RHE) [38][39][40]. Figure 4a shows the polarization curves for the OER of the CE, PE, 28%-HIE, and 28%-Si-HIE.…”
Section: Electrochemical Measurements For Oxygen Evolution Reaction (...mentioning
confidence: 99%